2013
DOI: 10.1002/cbf.2962
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyl terminus of Hsp70‐interacting protein (CHIP) is required to modulate cardiac hypertrophy and attenuate autophagy during exercise

Abstract: The carboxyl terminus of HSP70-interacting protein (CHIP) is a ubiquitin ligase/co-chaperone critical for the maintenance of cardiac function. Mice lacking CHIP (CHIP −/−) suffer decreased survival, enhanced myocardial injury, and increased arrhythmias compared to wild type controls following challenge with cardiac ischemia reperfusion injury. Recent evidence implicates a role for CHIP in chaperone-assisted selective autophagy, a process that is associated with exercise-induced cardioprotection. To determine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 99 publications
3
37
0
Order By: Relevance
“…Female mice were assigned to either unloaded (no resistance) wheel running or sedentary control groups, as described previously (54). Mice were randomly assigned to running or sham control groups and monitored in parallel by echocardiography on conscious mice using a Visual Sonics Vevo 770 and 2100 ultrasound biomicroscopy system at baseline, 2 wk, and 5 wk, as described previously (55,56).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Female mice were assigned to either unloaded (no resistance) wheel running or sedentary control groups, as described previously (54). Mice were randomly assigned to running or sham control groups and monitored in parallel by echocardiography on conscious mice using a Visual Sonics Vevo 770 and 2100 ultrasound biomicroscopy system at baseline, 2 wk, and 5 wk, as described previously (55,56).…”
Section: Methodsmentioning
confidence: 99%
“…The role of ubiquitin ligases in the regulation of IGF-I signaling in the myocardium in vivo is the latest in the growing literature implicating the ubiquitin proteasome system in maintenance of cardiac function (34,36). Mice lacking the ubiquitin ligase and protein chaperone carboxyl terminus of heat shock protein 70-interacting protein (CHIP) exhibit an exaggerated cardiac hypertrophy in as little as 1 wk and as much as 5 wk of running, which parallels increases in increased phosphorylated Akt after IGF-I stimulation in vitro (54). Although these studies suggest an inhibitory role of CHIP in Akt activation, Akt was not found to be a direct CHIP substrate, which has yet to be identified.…”
Section: Murf1tgϩmentioning
confidence: 99%
“…Mice in either diet group were allocated to an exercise intervention for 6 weeks as previously described (7,33). The groups were as follows: 1) regular diet (CTL); 2) CTL exercise (CTL-E); 3) Rosi; and 4) Rosi-E.…”
Section: Exercise Interventionmentioning
confidence: 99%
“…Autophagic flux was determined in vivo from the titration of bafilomycin A1 as previously described 24 . Antibodies for LC3B isoforms (Sigma-Aldrich #L7543) and beclin were used for western immunoblot analysis of markers of autophagy (Cell Signaling #3495P, Beverly, MA).…”
Section: Methodsmentioning
confidence: 99%
“…TaqMan gene expression assays (Life Technologies) were performed using universal TaqMan master mix (Life Technologies #4304437) commercial probes, as described previously 24 .…”
Section: Methodsmentioning
confidence: 99%